Hegels Metaphysics and the Philosophy of Politics - Thompson, Michael J. (Taylor and Francis, 2018)
The course of God : reading Hegel / Peter J. Steinberger -- The metaphysic of spirit and Hegel's philosophy of politics / Andrew Buchwalter -- Speculative logic as practical philosophy : political life in times of crisis / Angelica Nuzzo -- Metaphysics and the poverty of liberal-positivist political thought / Eric Goodfield -- The metaphysical infrastructure of Hegel's practical philosophy / Michael J. Thompson -- The metaphysics of rational action : Kantian and Aristotelian themes in Hegel's absolute idealism / Sebastian Stein -- Against the post-Kantian interpretation of Hegel : a study in proto-Marxist metaphysics / Michael Morris -- Objective spirit : Hegel's nonnative social ontology / Kevin Thompson -- Family structures as fields of historical tension : a case study in the relation of metaphysics and politics / Christopher Yeomans -- Hegel's metaphysics of marriage : teleology, ontology and sexually embodied freedom in the Philosophy of Rights account of the family / Joshua D. Goldstein -- Tiger stripes and embodied systems : Hegel on markets and models / David Kolb -- Hegel and the end of a particular historical development / Matthew J. Smetona.
Ebook published: 1 May 2018
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Metaphysik; Hegel, Georg Wilhelm Friedrich